Comparison of soil phosphorus fractions after 37 years of wheat production management practices in a semi-arid climate - Ncoyi, Khanyisile (University of the Free State, 2019)
Wheat production management practices are essential for optimum crop growth and the attainment of higher yields. However, these management practices have an impact on the sustainability of soil fertility and productivity. Therefore, it was important to investigate the impact of these residue management options on some soil fertility indicators such as phosphorus (P) fractions under a semi-arid climate. The aim of the study was to evaluate the influence of wheat residue management practices on soil P fractions in a long-term trial near Bethlehem in the Eastern Free State. The trial was established in 1979 and consisted of two methods of straw disposal (burned and unburned), three primary tillage methods (no-tillage, stubble mulch and ploughing) and two methods of weed control (chemical and mechanical). Representative soil samples were collected in 2016 at various soil depth intervals of 0-50, 50-100, 100-150 and 150-250 mm and analysed for soil P fractions. A sequential extraction procedure was used to differentiate between labile (0.5 M NaHCO3 extractable), moderately labile (0.1 M NaOH extractable), stable (1 M HCl extractable) and residual (concentrated HCl) fractions. Except for the residual P fraction, the total P (Pt) of the other fractions was separated into inorganic (Pi) and organic (Po) P. The straw disposal methods had variable influence on soil P fractions. Burning of wheat residues increased the labile Pi and hence Pt fractions when compared to the unburned residues across all four soil layers. However, the unburned plots had a slightly higher labile Po fraction than the burned plots except in the deepest soil layer (150-250 mm). In the moderately labile P fraction, burned residues resulted in a slightly higher Pi, Po and Pt compared to the unburned residues, except in the 0-50 mm (Pi) and 50-100 mm (Pi, Po and Pt) soil layers. Furthermore, burning of wheat residues increased the stable Pi, Po and Pt fractions when the unburned residues served as a reference. Conversely, the unburned plots had a slightly higher residual Pt fraction in the 0-50 and 50-100 mm soil layers. The tillage methods had a larger influence on soil P fractions than either straw disposal or weed control methods. No-tilled plots had higher labile Pi and Pt fractions, followed by stubble mulched plots and then by ploughed plots to a soil depth of 250 mm. On the other hand, ploughing increased the labile Po fraction followed by stubble mulch and then by no-tilled plots in all four soil layers. The no-tilled plots had higher moderately labile Pi and Pt, and residual Pt contents than either the stubble mulched or ploughed plots, particularly in the 0-50 mm soil layer. The chemical weeding method enhanced the labile and stable P fractions more than the mechanical weeding method to a soil depth of 250 mm. However, a reverse pattern was noted that the mechanical weeded plots had a slightly higher moderately labile Po, Pt and residual Pt. The combination of the no-tillage with chemical weeding had a significantly higher labile Pi than either stubble mulch or plough combined with mechanical weeding to a depth of 250 mm. No-tillage combined with either burning of wheat residues or chemical weeding increased the stable Pi fraction, particularly in the 50-150 mm soil layer. Burning of wheat residues combined with chemical weeding resulted to a higher moderately labile Pi compared to burned wheat residues combined with mechanical weeding in all four soil layers. Similarly, chemical weeding combined with burning of wheat residues enhanced the stable Pi fraction compared to mechanical weeding combined with burning of residues.
Dissertation (M.Sc. (Soil Science))--University of the Free State, 2019
Keywords: Phosphorus fractions; Straw disposal; Tillage method; Weed control; Wheat residues